Peran Pendidikan Karakter dalam Membangun Generasi Berintegrasi dan Beretika - Choirunnisa Choirunnisa; Desty Endrawati Subroto; Thia Atikah; Yosni Aulia; Siti Sukmawati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The era of globalization and digitalization brings new challenges in shaping the morals of the younger generation, such as the degradation of ethical values and the prevalence of unethical behavior in cyberspace. Character education is a strategic solution to build a generation with integrity and ethics. This study employs a literature review method with a systematic analysis of various scholarly sources related to character education from 2014 to 2024. The findings indicate that character education based on holistic values, such as wisdom, courage, and justice, has a positive impact on ethical behavior, academic achievement, and students' social interactions. The main challenges lie in the consistency of program implementation, the limited competencies of educators, and the lack of synergy among stakeholders. Moreover, the digital era demands character education integrating digital ethics to equip the younger generation with critical thinking skills and responsible media use. Through a collaborative approach, teacher training, and the development of relevant curricula, character education can create a generation that is not only intellectually intelligent but also morally mature.